Changes in the area at risk over time and following nicardipine administration in the dog. - Sandhu, Reena. (University of Ottawa (Canada), 1990)
A major determinant of myocardial infarct size (IS) is the amount of myocardium at risk of infarcting (AAR). When determined in vivo, AAR size depends upon the size of the normal perfusion territory of the occluded bed and upon collateral flow. We tested the hypothesis that AAR size can change spontaneously or after therapy. $\sp{\rm 99m}$Tc macroaggregates (MAC) or Monastral Blue Dye (MBD) were used to define the AAR. After MBD, the hearts were excised, sliced, photographed and incubated in Nitro-Blue tetrazolium to identify the infarct. After rephotographing, the slices were autoradiographed. The two sets of photographs and autoradiographs were used for planimetery of the AAR as defined by MBD, infarct size, and AAR as defined by MAC respectively. In all 3 groups there was a correlation between the AAR sizes as determined by the two techniques. In this model, the AAR size does not change either spontaneously or following Nicardipine. Nicardipine also does not appear to substantially limit infarct size. (Abstract shortened by UMI.)
Keywords: Health Sciences, Pharmacology.